Relaxation dynamics in the high-frequency crystal-field spectroscopy of PrNi5 point contacts - Balkashin, O. P.; Sukhodub, G. L.; Yanson, I. K.; Brill, T. M.; Jansen, A.G. M.; Wyder, ,P. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
High-frequency point-contact (PC) spectroscopy is used to investigate the relaxation processes kinetics in the intermetallic rare-earth compound PrNi5. A difference is observed in the spectral responsebetween the conventional low-frequency PC data and the response signal to microwave and farinfrared radiation of PrNi5-Cu point contacts. This difference is connected with the f-shell electronic levels (CEFlevels) and phonon temporal dynamics. The phonon reabsorption contribution to the spectra above the Debye energy decreases for microwave and far-infrared frequencies. However, the crystal-field contribution to the spectra at 4.2 meV is enhanced for high frequencies reflecting the relaxation processes specific for these Fermi-statistics electron excitations. The characteristic frequency for CEF-levelrelaxation is evaluated as ~200 GHz.